The Broadband Futures Forum: Affordability of Broadband Services - Campbell, Leith H; Mithen, Johanna (Journal of Telecommunications and the Digital Economy, 2021)
On 25 August 2021, TelSoc hosted the ninth Broadband Futures Forum, held online, to discuss the affordability of broadband services in Australia. A panel of four speakers, drawn from broadband providers and social policy advocates, outlined their experiences with affordability and digital inclusion. Discussion following the speeches ranged over the topics of a broad social policy response, the definition of affordability in relation to financial hardship, the provision of public Wi-Fi, and the availability of suitable devices.